Inventory Analysis using Multi-Criteria ABC and ISM Method – A Case Study in Indonesia’s Aviation MRO - Dita Pradini; Ratih Dyah Kusumastuti (PT Mattawang Mediatama Solution, 2024)
Level of inventory plays a crucial role in managing the supply chain in a company, one of which is Aircraft Maintenance, Repair, and Overhaul (MRO) Company. This paper will analyze the material inventory in one of Indonesia’s aircraft MRO companies by categorizing the material and focus on finding the root causes of the high inventory level. ABC Analysis using multiple criteria will be used to categorize the aircraft spare parts inventory. The categories will then be used as the Focus Group Discussion (FGD) topic to gain and determine several root causes of the phenomena. FGD results will then be further analysed using Interpretative Structural Matrix (ISM) to see if there are some interrelationships between root causes. The high inventory level of aircraft spare parts inventory root causes will be specifically determined by analyzing the A category of ABC Classification as this category represents 70% of the inventory. Based on the analysis, it is recommended to solve the root causes extracted from the ISM first to lower the inventory level. This study will be useful for managers to determine the strategy to make the inventory lower impacting on the increase of company’s profit increase.